2019
DOI: 10.1073/pnas.1821216116
|View full text |Cite
|
Sign up to set email alerts
|

Probing initial transient oligomerization events facilitating Huntingtin fibril nucleation at atomic resolution by relaxation-based NMR

Abstract: The N-terminal region of the huntingtin protein, encoded by exon-1, comprises an amphiphilic domain (httNT), a polyglutamine (Qn) tract, and a proline-rich sequence. Polyglutamine expansion results in an aggregation-prone protein responsible for Huntington’s disease. Here, we study the earliest events involved in oligomerization of a minimalistic construct, httNTQ7, which remains largely monomeric over a sufficiently long period of time to permit detailed quantitative NMR analysis of the kinetics and structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(136 citation statements)
references
References 46 publications
14
122
0
Order By: Relevance
“…These observations suggest that S13 phosphorylation primes phosphorylation at S16, similar to what has been shown for other proteins. [18,44] Additionally, these findings were in accordance with our previous cellular and in vivo observation where we showed that TBK1 phosphorylated mainly S13. [28] Figure 6.…”
Section: Real-time Monitoring Of Tbk1 Phosphorylation Of Httex1 Suggesupporting
confidence: 92%
“…These observations suggest that S13 phosphorylation primes phosphorylation at S16, similar to what has been shown for other proteins. [18,44] Additionally, these findings were in accordance with our previous cellular and in vivo observation where we showed that TBK1 phosphorylated mainly S13. [28] Figure 6.…”
Section: Real-time Monitoring Of Tbk1 Phosphorylation Of Httex1 Suggesupporting
confidence: 92%
“…4 A and B, cyan circles), the CTD domain was represented by an ensemble of varying size (N), ranging from 1 to 8 (46,47). Since the population of the closed state giving rise to the interdomain PREs is unknown a priori, we made use of a PRE target function that maximizes the correlation coefficient between observed and calculated PREs (48). The PRE data were supplemented by highly ambiguous distance restraints (49) from all atoms of residues 34 and 36 in the JD domain, identified from 15 N CPMG relaxation dispersion experiments (see following section) to be involved in interdomain contacts, to the atoms of all residues in the CTD domain.…”
Section: Resultsmentioning
confidence: 99%
“…A number of in vitro experiments have established that the formation of fibrillar aggregates by proteins bearing polyQ tracts can proceed via oligomers 55 , potentially liquid-like 56 , stabilized by intermolecular interactions between flanking regions of polyQ tracts and equivalent to those stabilizing coiled coils 2,57,58 . In proteins bearing polyQ tracts such as huntingtin 59,60 and AR 20,21 extending the length of the tract increases its helicity and, as we have now shown, that of the sequence immediately flanking them at the N terminus.…”
Section: Discussionmentioning
confidence: 99%